2019
DOI: 10.3390/w11040748
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved and Particulate Organic Carbon in Icelandic Proglacial Streams: A First Estimate

Abstract: Here for the first time, we analyze the concentration of dissolved (DOC) and particulate organic carbon (POC), as well as its optical properties (absorbance and fluorescence) from several proglacial streams across Iceland, the location of Europe’s largest non-polar ice cap. We found high spatial variability of DOC concentrations and dissolved organic matter (DOM) composition during peak melt, sampling 13 proglacial streams draining the 5 main Icelandic glaciers. Although glacial-derived organic matter (OM) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Typically, glacier DOM is associated with low SUVA254 (1.77 ± 1.16 L mg C -1 m -1 , n = 5) and high FI values (1.52 ± 0.09, n =11; Fegel et al 2016;Fellman et al 2014;Stubbins et al 2012). Similarly, parallel factor analysis of glacier DOM has shown that protein-like fluorophores dominate (typically > 70 %) total fluorescence (Chifflard et al 2019;Hood et al 2009;Kellerman et al 2020;Pautler et al 2012;Smith et al 2018;Stubbins et al 2012;Zhou et al 2019b). The broad shifts in optical and isotopic DOM properties, together with streamwater  O, likely reflected shifting sources of DOM and streamwater with time since glacier retreat.…”
Section: Geochemical Setting and Bulk Dissolved Organic Matter Propertiesmentioning
confidence: 99%
“…Typically, glacier DOM is associated with low SUVA254 (1.77 ± 1.16 L mg C -1 m -1 , n = 5) and high FI values (1.52 ± 0.09, n =11; Fegel et al 2016;Fellman et al 2014;Stubbins et al 2012). Similarly, parallel factor analysis of glacier DOM has shown that protein-like fluorophores dominate (typically > 70 %) total fluorescence (Chifflard et al 2019;Hood et al 2009;Kellerman et al 2020;Pautler et al 2012;Smith et al 2018;Stubbins et al 2012;Zhou et al 2019b). The broad shifts in optical and isotopic DOM properties, together with streamwater  O, likely reflected shifting sources of DOM and streamwater with time since glacier retreat.…”
Section: Geochemical Setting and Bulk Dissolved Organic Matter Propertiesmentioning
confidence: 99%
“…Nitrogen was also observed to decline in downstream glacial lakes in North America [ 199 ]. However, DOC increased during its flow in proglacial streams in Iceland, probably due to carbon mineralization and microbial transformation [ 212 ]. These contrasting results show how the processes in the proglacial streams are regulated by many local factors.…”
Section: Proglacial Systemsmentioning
confidence: 99%
“…DOC and POC fluxes from a drained peatland in west Iceland (Borgarfjörður region) were quantified at 11.65 (± 1.98) and 9.57 (± 6.21) g m -2 yr -1 , making up 2.82 and 2.31% of the local carbon budget, respectively (Ólafsdóttir, 2015). In 13 proglacial streams in central and southwest Iceland DOC concentrations ranged from 0.11 to 0.94 (mean: 0.226) mg L -1 and POC concentrations ranged between 0.67 and 84.67 (mean: 0.37) mg L -1 (high POC concentrations were linked to high anthropogenic influences), resulting in an estimated DOC flux of 0.008 ± 0.002 Tg yr -1 from Icelandic glaciers (Chifflard et al, 2019). Kardjilov et al (2006) quantified fluvial organic carbon fluxes from three large inland catchments in NE Iceland, where DOC (0.23-0.30 g C m -2 yr -1 ) and POC (0.23-0.44 g C m -2 yr -1 ) fluxes were relatively low and close to detection limits.…”
Section: Introductionmentioning
confidence: 99%